Negosiasi Islam dan Budaya Jawa dalam Ruang Sosial-Religius - Pranata, Anillahi Januar Adi; Munir, M. (Postgraduate Studies UIN Sunan Ampel Surabaya, 2024)
The Javanese Muslim community is closely connected to the traditions that continue to thrive within society today. The interaction between Islam and local culture and traditions reflects the distinctive characteristics of religious life that have developed in Indonesia, particularly in Java. Thus, the relationship between Islam and Javanese culture and tradition represents two inseparable aspects that are continuously interrelated. Based on this, the study examines the understanding of Javanese Islam by exploring the relationship between culture and religion. Intellectualism within Javanese Islam originates from pre-existing traditions and cultural practices that were later refined and harmonized with Islamic values. A culture is considered acceptable in Islam when it embodies meaningful processes and rituals that do not contradict Islamic principles, while also reflecting noble Islamic values and contributing positively to the Muslim community.